التسامح كمتغير منبئ بالإقبال علي الحياة والاندماج الاجتماعي لدي عينتين من المراهقين المعاقين بصريا والمعاقين سمعيا - حسام أحمد, أبو سيف محمد إسماعيل; القحطاني, عبد الله بن صالح (Sciences de l'Homme et de la Société; Vol. 24 (2017): SCIENCE DE L'HOMME ET DE LA SOCIETE (Sep 2017), 2017)
هدفت الدراسة الحالية الوقوف علي سلوك التسامح كمتغير منبئ بالإقبال علي الحياة والاندماج الاجتماعي لدي عينتين من المراهقين المعاقين بصريا والمعاقين سمعيا، وذلك علي عينة مكونة من (40) معاق تم تقسيمهم:20 من المراهقين المعاقين بصريا المتواجدين بمعهد النور بالرياض، و20 من المراهقين المعاقين سمعيا بمعهد الأمل، وقد استخدم الباحثان الأدوات الآتية: مقياس التسامح (زينب شقير2010م)، مقياس الإقبال علي الحياة (تحية عبد العال ورمضان مظلوم2013م)، ومقياس الاندماج الاجتماعي (من إعداد الباحثين،2015م)، توصلت الدراسة إلي عدة نتائج أهمها: وجود علاقة ارتباطيه دالة إحصائياً بين التسامح وكل من الإقبال علي الحياة والاندماج الاجتماعي لدي عينة البحث، أيضا يمكن التنبؤ من خلال التسامح بالإقبال علي الحياة والاندماج الاجتماعي لدي عينة البحث، أخيرا وجد البحث أن هناك فروق دالة إحصائياً بين المعاقين بصرياً والمعاقين سمعياً في التسامح والإقبال علي الحياة والاندماج الاجتماعي. Abstract : The present study aimed at identifying the behavior of tolerance as a variable predictor of the relationship between have two samples of teenagers visually impaired and hearing-impaired, so a sample of (40) with a disability were divided: 20 teenagers visually impaired, and 20 teenagers hearing impaired, to reach the objective of the study researchers used the following tools: Tolerance scale (ZainabShuqayr 2010), turnout life scale (Taheya Abdel Aal and Ramadan Mazloum, 2013), and the measure of social integration (prepared by researchers.2015), study found several conclusions, including:The presence of correlation statistically significant between tolerance and all of the interest in life and social integration in a sample search, also predictable through tolerance, the popularity on the life and social integration in a sample search, finally research found statistically significant differences visually impaired and hearing-impaired in tolerance and the popularity of life and social integration.